The relationship of financial advisors' outward presentation and client acquisition of selected insurance companies in Tacloban City - Mina, Ma. Angelique M.; Morillo, Yasmin Crystha M.; Oriondo, Yanna Alexis O.
The findings indicate a shared acknowledgment among financial advisors and insurance companies regarding the significant impact of outward presentation on client acquisition. Financial advisors recognize that their presentation plays a pivotal role in shaping initial client perceptions and influencing their decision-making process. Insurance companies, in turn, emphasize the importance of equipping advisors with the necessary skills to effectively communicate and build relationships with clients.